ATTITUDE OF PREGNANT WOMEN IN CHOOSING THE TYPE OF DELIVERY: A QUALITATIVE STUDY - Ghelichkhani, Samereh; Masoumi, Seyedeh Zahra; Oshvandi, Khodayar; Kazemi, Farideh; Ebadian, Mohammad Reza (Journal of Postgraduate Medical Institute, 2021)
Objective: To find out the attitude of women to the choice of type of delivery Methodology: This qualitative study was conducted from June 2018 to July 2019 in Hamedan university of Medical Sciences. 12 pregnant women participated in this study. Data were analyzed with qualitative content analysis Results: We extracted two themes including “tendency toward vaginal delivery” with six categories: Lower rate of maternal and neonatal complications, Fear of cesarean section, Positive experiences of relatives, Maternal and neonatal benefits, improved techniques for enhancing the quality, Social and emotional support for mothers and “tendency toward cesarean section delivery” with five categories: Materna/l complications of vaginal delivery, Concerns about inappropriate behavior of treatment team, Physical environment and equipment, Negative experiences of relatives, Concerns about different aspects of infant health. Conclusion: Based on the results obtained from the findings of the study, the correct implementation of empowerment programs for maternity wards to reduce maternal and infant complications, improve the quality of maternity preparation classes, implement standard and appropriate pain relief techniques, improve social and psychological support for mothers And promoting respectful behaviors during the treatment of pregnant women with standard physical spaces and sufficient equipment can help pregnant women in choosing the type of delivery.